Optimalisasi Layanan Administrasi Perdata melalui Penerapan User Centered Design pada Desain Antarmuka Digital di Pengadilan Negeri Bale Bandung - Nursyanti, Reni; M. Tonny Heru Susanto; Muhammad Fajar Romadhon, Fajar; Muhammad Qaysa Al Haq, Qaysa; Dimyati, Ahmad (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
The management of civil case administration services at the Bale Bandung District Court still faces challenges in terms of efficiency and public accessibility. This Community Service Program (PkM) aims to assist the partner in optimizing service governance through the design of a digital application interface based on the User Centered Design (UCD) approach. The implementation method includes needs analysis, interface design using UCD principles, prototype testing, and user training for related staff. The results of the program show the development of a more intuitive and user-friendly digital application interface that meets user needs, thereby improving service efficiency and providing a better experience for the community. This PkM activity not only offers a practical solution for the partner but also contributes to supporting digital transformation in the field of civil administration services.